Learning Heat and Its Transfer with Power Point Learning Media for Grade V Students of Elementary School - Rozali, Dini; Ramadan, Zaka Hadikusuma (Universitas Pendidikan Ganesha, 2021)
Currently, media used as one of the learning components had not been fully used and developed according to the needs. The current characteristics and conditions and the teaching-learning process were fixated only on student textbooks. The purpose of this research was to develop Powerpoint learning media for learning 3,4 and 5 on theme 6